2015
DOI: 10.1016/j.bjorl.2014.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric and anthropometric data of obstructive apnea in different age groups

Abstract: Cephalometric measurements MP-H and PNS-P and cervical and waist circumferences correlated with obstructive sleep apnea syndrome severity in patients in the ≥40 and <60 age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 39 publications
(83 reference statements)
0
10
1
2
Order By: Relevance
“…Cephalometric performed by means of lateral teleradiography has been shown to be an important instrument in the multidisciplinary field for evaluating the upper airways [ 13 , 14 ] because it is easily accessible and low cost, highly reproducible, and the individual is submitted to a low dose of radiation [ 4 , 15 ]. Thus, innumerable studies have sought associations of the physical characteristics related to these airway spaces, as a way of predicting pathologies [ 13 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cephalometric performed by means of lateral teleradiography has been shown to be an important instrument in the multidisciplinary field for evaluating the upper airways [ 13 , 14 ] because it is easily accessible and low cost, highly reproducible, and the individual is submitted to a low dose of radiation [ 4 , 15 ]. Thus, innumerable studies have sought associations of the physical characteristics related to these airway spaces, as a way of predicting pathologies [ 13 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in the literature about changes in the upper airways resulting from orthodontic treatment, orthognathic surgery or in individuals diagnosed with sleep apnea [ 4 7 ]; however, few studies have shown evidence of the airspace related to facial types and Angle Class I individuals, and this information is relevant to assist in orthodontic planning.…”
Section: Introductionmentioning
confidence: 99%
“…Los estudios cefalométricos para el estudio de la forma y caracteristicas del componente cráneo-maxilomandibular, son muy utilizados en el anáisis de sujetos con deformidades faciales y en la correlación con algunas patologías, como la apnea del sueño (Borges et al, 2015) y la calcificaciones de tejidos blandos (Garay & Olate, 2013), entre otras. Sujetos con respiración bucal por obstrucción de vía aérea superior muestran cambios en los análisis, por ejemplo, en el ángulo maxilomandibular (Pulido Valladares et al, 2012).…”
Section: Introductionunclassified
“…This process is labor and resource intensive and time consuming, leading to a limited number of available appointment slots in most hospitals. Because of these limitations, various alternative diagnostic techniques (such as the Mueller maneuver, 5,6 x-ray cephalometry, [7][8][9][10][11][12] upper airway endoscopy during sleep and sedated sleep) have been proposed as alternatives. [13][14][15][16][17] The potential benefits of these methods over simple clinical assessment remain under discussion.…”
mentioning
confidence: 99%